Intravenous and Oral Fluid Therapy in Neonatal Calves With Diarrhea or Sepsis and in Adult Cattle - Constable, Peter D.; Trefz, Florian M.; Sen, Ismail; Berchtold, Joachim; Nouri, Mohammad; Smith, Geoffrey; Grünberg, Walter (Frontiers in Veterinary Science, 2021)
Optimal fluid therapy protocols in neonatal calves and adult cattle are based on consideration of signalment, history, and physical examination findings, and individually tailored whenever laboratory analysis is available. Measurement of eye recession into the orbit, skin tent duration in the lateral cervical region, and urine specific gravity by refractometry provide the best estimates of hydration status in calves and cattle. Intravenous and oral electrolyte solutions (OES) are frequently administered to critically ill calves and adult cattle. Application of physicochemical principles indicates that 0.9% NaCl, Ringer’s solution, and 5% dextrose are equally acidifying, lactated Ringer’s and acetated Ringer’s solution are neutral to mildly acidifying, and 1.3-1.4% sodium bicarbonate solutions are strongly alkalinizing in cattle. Four different crystalloid solutions are recommended for intravenous fluid therapy in dehydrated or septic calves and dehydrated adult cattle: 1) lactated Ringer’s solution and acetated Ringer’s solution for dehydrated calves, although neither solution is optimized for administration to neonatal calves or adult cattle; 2) isotonic (1.3%) or hypertonic (5.0% or 8.4%) solutions of sodium bicarbonate for the initial treatment of calves with diarrhea and severe strong ion (metabolic) acidosis and hyponatremia, and adult cattle with acute ruminal acidosis; 3) Ringer’s solution for the treatment of strong ion (metabolic) alkalosis in dehydrated adult cattle, particularly lactating dairy cattle; and 4) hypertonic NaCl solutions (7.2%) and an oral electrolyte solution or water load for the rapid resuscitation of dehydrated neonatal calves and adult cattle. Knowledge of the requirements for the ideal OES for diarrheic calves continues to evolve, and much progress has been made over the last 40 years. The critical issues in formulating the ideal OES for neonatal calves are osmolality, sodium concentration, the effective SID that reflects the concentration of alkalinizing agents, and the energy content. The last three factors are intimately tied to solution osmolality and the rate of abomasal emptying, and therefore the rate of sodium delivery to the small intestine and ultimately the rate of resuscitation. Formulation of a practical, effective, inexpensive and commercially available OES for adult ruminants remains an important need in fluid and electrolyte therapy.